Branding Vocational School with The Internet of Things (IoT) Production Competency of Students in Indonesia - Willyarto, Mario Nugroho; Paramitha, Rizka Yona (LSPR Institute of Communication & Business, 2023)
There are many creative opportunities for Internet of Things (IoT) systems to positively impact schools, industries, and others. The purpose of this study is to describe how negative issues in vocational schools (SMK) can be overturned with the ability of SMK students in the field of IoT. Researchers used a qualitative approach with descriptive methods. The results show that vocational schools in Indonesia prepared students to face the world of work supporting IoT learning such as curriculum synchronization, laboratories, and production units. Optimism that IoT will be the flagship of vocational school because the SMK has competent human resources in IoT technology and has been certified. A vocational school is producing the IoT smart lock RFID system products. The conclusion is although the IoT system is still straightforward, which is made in the form of a smart lock system, it can represent technology products made by vocational students. This can be a school branding for prospective students or their parents.